A pilot test for establishing validity and reliability of qualitative interview in the blended learning English proficiency course - Abd Gani, Nurul Imtiaz (2020)
Qualitative interview data is commonly used in the field of social sciences as it involves collection of data between the interviewer and interviewee via verbal interaction. However, the issue of qualitative is mostly related to the validity and reliability of its data especially for inexperience researchers to perform a systematic procedure of conducting the interview session. A pilot test is also one of the procedures that need to be mastered by a researcher in collecting qualitative data as it may assists in the improvisation to the actual interview. The paper aims to describe the process of conducting the pilot test to determine the validity of the qualitative data for a study on factors related to learners’ satisfaction in blended learning English proficiency courses. Moreover, this study will also provide a better understanding on the importance of piloting interview instrument. The semi-structured interview was selected and tested on the first year undergraduates’ learners in English proficiency course. Based on the result of the pilot test, it showed that the instrument can be considered valid and reliable, and at the same time allowing opportunity for refinements and modifications in the research tool.